Angiotensin II Type-1 Receptor Antibody in Solid Organ Transplantation – Is It Time to Test? - Paul James Patrick Martin; Paul James Patrick Martin; Michelle Willicombe; Michelle Willicombe; Candice Roufosse; Candice Roufosse (Transplant International)
Angiotensin II type-1 receptor antibody (AT1R-Ab) has been mooted as a potential effector of both acute and chronic antibody mediated rejection (AMR). A growing body of literature on the topic is now coming under scrutiny in the context of the evolving Banff AMR diagnostic classification system and refinement of recommendations for histocompatibility testing by the Sensitization in Transplantation Assessment of Risk (STAR) workgroup. This mini-review discusses the latest understanding of pathophysiological mechanisms, clinical evidence for the pathogenicity of AT1R-Ab, and methods of laboratory testing.